2019
DOI: 10.1097/ijg.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

Ab Interno Trabeculotomy: Key Prognostic Factors

Abstract: Précis: The preoperative factors associated with a decreased survival rate of ab interno trabeculotomy (AbIT) perfomed using a Trabectome in open-angle glaucoma were selective laser trabeculoplasty (SLT) performed previously and axial length (AL) over 23.82 mm. Purpose: The purpose of this study was to find preoperative factors that predict outcomes of AbIT by a Trabectome. Materials and Methods: This retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
6
2
Order By: Relevance
“…Thus, we may have missed other factors that potentially contributed to surgical success or failure. For instance, a recent study suggested an inverse relationship between the longer axial length and preoperative corneal hysteresis (Kuusniemi et al 2020;Tracer et al 2021), which was not measured in the present study. Additionally, almost one-third of the patients with lTLO were excluded from our statistical analysis for various reasons, which may have also held some selection bias.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Thus, we may have missed other factors that potentially contributed to surgical success or failure. For instance, a recent study suggested an inverse relationship between the longer axial length and preoperative corneal hysteresis (Kuusniemi et al 2020;Tracer et al 2021), which was not measured in the present study. Additionally, almost one-third of the patients with lTLO were excluded from our statistical analysis for various reasons, which may have also held some selection bias.…”
Section: Discussioncontrasting
confidence: 80%
“…However, various pre-and perioperative backgrounds are known to affect the surgical outcomes of category 1 MIGS and ab externo TLO. For example, high preoperative IOP (Jea et al 2012;Ahuja et al 2013;Okeke et al 2017;Tojo et al 2017;Esfandiari et al 2019;Kono et al 2020) and previous selective laser trabeculoplasty (Ahuja et al 2013;Shoji et al 2016;Tojo et al 2017;Kuusniemi et al 2020) have been reported to be risk factors for surgical failure, whereas elderly age (Tanito et al 2002;Jea et al 2012;Ahuja et al 2013) and combined cataract surgery (Tanito et al 2002;Ting et al 2012;Ahuja et al 2013;Dang et al 2016;Tojo et al 2017;Hara et al 2019;Kono et al 2020) have been estimated to contribute to good surgical outcomes. In terms of the glaucoma type, steroid-induced glaucoma (Steroid G) is more likely to be associated with surgical success (Iwao et al 2011;Dang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Our study was not sufficiently powered to assess other possible outcome factors such as axial length and state after SLT. 23 …”
Section: Discussionmentioning
confidence: 99%
“…If the main outflow resistance were distal to the collector channel, canal-based MIGS may be ineffective; thus, a longer axial length may cause elongation of the aqueous vein, thereby increasing aqueous venous pressure. Kuusniemi et al reported that a history of SLT before canal-based MIGS was a risk factor for surgical failure, 23 , 24 and while it is easy to recognize that canal-based MIGS might not be effective in patients resistant to SLT, no studies have reported a longer axial length to be a risk factor for SLT failure; therefore, further investigation is required.…”
Section: Discussionmentioning
confidence: 99%